Tests of sewer pipelines differentiated in terms of the assessment of their technical condition - Kuliczkowski, Andrzej; Lisowska, Justyna (Instal, 2024)
Based on the latest knowledge on existing diagnostic devices for testing the technical condition of sewers, a division of research methods into four groups was proposed. They are differentiated by the scope of the assessment of their technical condition and, at the same time, by the costs and time period of the tests performed. Information was provided on which method should be used in order to obtain more or less precise knowledge about the technical condition of sewage pipes.